Developing a framework for initial teacher education: route map or reflective tool?. Issue 2 (15th March 2022) - Knight, Rupert; Sullivan, Stefanie
ABSTRACT: Initial Teacher Education (ITE) is inherently complex. Challenges include the uncertain nature of teacher knowledge, the need to learn in both practical and theoretical contexts and the developmental journey of the beginning teacher. While one response to this complexity is greater standardisation, another is to foster thinking, autonomous professionals. Attempting to reconcile these tensions and provide a coherent ITE experience, one School of Education introduced an overarching framework of strands of content and phases of the training year. Beginning teachers, from both Primary and Secondary one-year postgraduate teaching routes, shared their experiences of this framework in a series of focus groups at different points in their training. Responses suggest that the framework does provide a valuable guiding structure and stimulus for reflection, though potential for use in school and in the latter stages of the course is yet to be completely fulfilled. In view of the individual trajectories of the beginning teacher, it is argued that future development might focus more on the framework's value as a reflective tool in both university and school settings, rather than as a formal route map for teacher learning.